Problems of the Fans Economy and Countermeasures for Its Governance - Hsu, Yu-Hsien (Asia Pacific Economic and Management Review, 2026)
With the development of media and the economy, "idol chasing" has become a common social phenomenon. Different age groups, regions, and circles have their own ways of chasing idols. These ways range from real-time interactions on short-video platforms and Weibo updates to participation in offline concerts and fan meetings; from teenagers’ consumption of idol merchandise and albums to adults’ participation in social public welfare services in the name of being stars’ fans. Idol chasing has become an important carrier that penetrates the daily life of the public and is related to cultural communication and economic consumption. Undoubtedly, it has driven the economic market, activated the vitality of the consumer market, and also brought positive effects to cultural communication. However, at the same time, there are also some negative impacts in society, such as irrational support activities, public order chaos, and ticket scalping.